2008
DOI: 10.1186/1475-2891-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Commercial weight loss diets meet nutrient requirements in free living adults over 8 weeks: A randomised controlled weight loss trial

Abstract: ObjectiveTo investigate the effect of commercial weight loss programmes on macronutrient composition and micronutrient adequacy over a 2 month period.DesignAdults were randomly allocated to follow the Slim Fast Plan, Weight Watchers Pure Points Programme, Dr Atkins' New Diet Revolution, or Rosemary Conley's "Eat Yourself Slim" Diet & Fitness Plan.SettingA multi-centre randomised controlled trial.Subjects293 adults, mean age 40.3 years and a mean BMI 31.7 (range 27–38) were allocated to follow one of the four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Reductions in carotenoid intakes and plasma concentrations were reported after an Atkins diet, while there were increases in carotenoid intakes and plasma concentrations after a “Paleolithic” diet . The “Paleolithic” diet also showed an increase in vitamin C intake, reflecting advice to consume more fruits than typical Atkins diets, which mostly showed reductions in vitamin C intakes (Figure ). However, one trial with a modified Atkins diet showed an increase in plasma vitamin C concentration, probably because fruit juice was included in the meals provided …”
Section: Discussionmentioning
confidence: 99%
“…Reductions in carotenoid intakes and plasma concentrations were reported after an Atkins diet, while there were increases in carotenoid intakes and plasma concentrations after a “Paleolithic” diet . The “Paleolithic” diet also showed an increase in vitamin C intake, reflecting advice to consume more fruits than typical Atkins diets, which mostly showed reductions in vitamin C intakes (Figure ). However, one trial with a modified Atkins diet showed an increase in plasma vitamin C concentration, probably because fruit juice was included in the meals provided …”
Section: Discussionmentioning
confidence: 99%
“…Across several studies that evaluated micronutrient adequacy, many of the micronutrients that consistently fell short of the recommended daily intake are essential for metabolism, energy, and bone health (B vitamins, iron, calcium, and magnesium) [20][21][22]. The caveats of these studies are that food records were often self-reported and the studies included selected groups (ie, overweight, obese) who usually tend to inaccurately report their true food intakes.…”
Section: Mrs and Micronutrients Adequacymentioning
confidence: 97%
“…In a recent trial designed to evaluate individuals' ability to adjust to diet routines, free-living overweight and obese adults were able to adapt to four different popular commercial diet programs with fairly minimal, if any, professional guidance [20]. All intervention groups showed variable micronutrient inadequacies, except for the diet plan that included MRs. That arm showed only a decline in niacin (95% of recommended), but adequate other micronutrients similar to baseline.…”
Section: Mrs and Micronutrients Adequacymentioning
confidence: 98%
“…A few longitudinal studies have examined the association between changes in dietary patterns and a reduction in BMI (12)(13)(14)(15)(16) . There is evidence in the literature that several web-based weight-loss interventions are efficient at supporting weight loss (17)(18)(19)(20)(21)(22)(23)(24) . In this regard, these programmes can support participants by identifying dietary patterns and can also be used for collecting precise long-term and comprehensive nutrition data (25) .…”
mentioning
confidence: 99%